Purchasing involvement in technologically uncertain new product development projects: Challenges and implications. Issue 3 (June 2019) - Mikkelsen, Ole S.; Johnsen, Thomas E.
Abstract: This paper explores an emerging field of research within purchasing that concerns the changing role of purchasing when companies embark on technologically uncertain NPD projects. Where existing research has examined the role of purchasing in facilitating early supplier involvement in new product development, little research has been done to date on how purchasing's role might change when facing technologically uncertain NPD that require new capabilities and new technology. Based on an in-depth case study of a technologically uncertain NPD project in the passenger ship rescue equipment industry, the paper sheds light on how supplier involvement in NPD projects with a high degree of technological uncertainty impacts on a company's sourcing strategies and the challenges this poses for purchasing. Based on the case study findings, we propose a) that early purchasing involvement in technologically uncertain NPD projects requires a mature purchasing organization that possesses competences to interact effectively with R&D and b) that involving a new supplier from a different industry in NPD projects characterized by technological uncertainty requires a leap of faith from both innovating firm and supplier. The paper contributes to research in early supplier involvement in new product development, in particular the thin branch within this body of literature that now focuses on early purchasing involvement. Highlights: The changing role of purchasing during technologically uncertain new product development. In-depth case study analysis from maritime safety industry. Early purchasing involvement in technologically uncertain NPD projects requires a mature purchasing organization. Involving a supplier from a different industry requires a leap of faith from both parties. Contributes to emerging research on early purchasing involvement.